Negligible import of enteric pathogens by newly arrived asylum seekers and no impact on incidence of notified Salmonella and Shigella infections and outbreaks in Rhineland-Palatinate, Germany, January 2015 to May 2016 - Ehlkes, Lutz; Zanger, Philipp (Eurosurveillance, 2018)
Introduction The 2015 refugee crisis raised concerns about an import of infectious diseases affecting the German population. Aims: To evaluate public and individual health benefits of stool screening, and explore whether importation of enteric pathogens by newly arrived asylum seekers impacts on the host population. Methods: We used data from mandatory stool screening to determine the overall, age, sex, and country-specific prevalence of enteric bacteria and helminths. We used surveillance data to assess whether the number of incoming asylum seekers influenced notifications of salmonellosis and shigellosis in Rhineland-Palatinate. Results: Salmonella were found in 0.2% (95% confidence interval (CI) 0.2-0.3%) of 23,410 samples collected from January 2015 to May 2016. Prevalence was highest in children under 5 years (0.8%; 95% CI: 0.5-1.3%). No Shigella or invasive Salmonella spp. were detected. In a subset of 14,511 samples, the prevalence of helminth infestation was 2.4% (95% CI: 2.1-2.6%), with highest proportions detected in adolescents (4.6%; 95% CI 3.8-5.4%) and among Eritreans (9.3%; 95% CI: 7.0-12.0%); in the latter particularly Schistosoma mansoni and Taenia spp. The increase in asylum applications did not increase notifications of salmonellosis and shigellosis. No transmission from asylum seekers to German residents was notified. Conclusion: Public health risk associated with imported enteric pathogens is very low overall. Addressing individual and public health risks, we recommend replacing stool screening of all newly arrived asylum seekers by a targeted approach, with target groups and approaches being adapted if necessary. Target groups supported by our data are children, adolescents, and Eritreans.
Gesehen am 26.07.2019